The New States of Central Asia and their Neighbours (London Pinter, 1994)
An account of changes inside the five Central Asian republics of the former Soviet Union and the impact these changes have had on neighbouring countries including: Russia, Turkey, Iran, Saudi Arabia, Afghanistan, India, Pakistan and China.
Keywords: Asia, Central -- Diplomatic relations -- Asia, Central -- Foreign relations -- 1991-